Influence of Framework Silica to Alumina Ratio on the Sorption Characteristics of Synthetic Large-Port Mordenites - A.A. Shaikh; P.N. Joshi; H.S. Soni; V.P. Shiralkar (Adsorption Science & Technology)
Synthetic large-port mordenite samples with different framework SiO 2 /Al 2 O 3 ratios (ranging from 10 to 35) obtained by direct hydrothermal crystallization were studied using different probe molecules. The influence of the framework aluminium content on the BET surface area and the micropore void volume in large-port mordenites was examined using low-temperature nitrogen sorption. Sorption uptake using different probe molecules such as water, benzene, n-hexane and cyclohexane was measured on the protonic form of the mordenite samples. The sorption energetics in large-port mordenites as a function of framework SiO 2 /Al 2 O 3 ratio was discussed on the basis of the isotherms for water sorption over the temperature range 303–403 K. The sorption data were analyzed in terms of different models of sorption isotherm equations. The wide variation in the isosteric heats of sorption of polar but amphoteric water molecules exhibited by mordenite samples with different framework Si/Al ratios demonstrate the heterogeneous character of the surface.